2006
DOI: 10.1093/nar/gkj458
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid binding and chaperone properties of HIV-1 Gag and nucleocapsid proteins

Abstract: The Gag polyprotein of HIV-1 is essential for retroviral replication and packaging. The nucleocapsid (NC) protein is the primary region for the interaction of Gag with nucleic acids. In this study, we examine the interactions of Gag and its NC cleavage products (NCp15, NCp9 and NCp7) with nucleic acids using solution and single molecule experiments. The NC cleavage products bound DNA with comparable affinity and strongly destabilized the DNA duplex. In contrast, the binding constant of Gag to DNA was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
188
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(206 citation statements)
references
References 87 publications
18
188
0
Order By: Relevance
“…Therefore, the increase in transition width depends linearly on protein concentration at low fractional binding. We have used our measurement of the concentration dependence of the transition width to quantify the association constant for NC to DNA, and determined a value of K a = (1.22 ± 0.25) x10 8 M −1 for NC binding to the DNA lattice in 50 mM Na + solution, in agreement with bulk measurements of this quantity (21). The large increase in the transition width induced by HIV-1 NCp7 is probably related to its sequence-specific preferential binding to ssDNA, as well as to the change of DNA elasticity upon binding of NC to ssDNA or dsDNA.…”
Section: Introductionsupporting
confidence: 53%
See 1 more Smart Citation
“…Therefore, the increase in transition width depends linearly on protein concentration at low fractional binding. We have used our measurement of the concentration dependence of the transition width to quantify the association constant for NC to DNA, and determined a value of K a = (1.22 ± 0.25) x10 8 M −1 for NC binding to the DNA lattice in 50 mM Na + solution, in agreement with bulk measurements of this quantity (21). The large increase in the transition width induced by HIV-1 NCp7 is probably related to its sequence-specific preferential binding to ssDNA, as well as to the change of DNA elasticity upon binding of NC to ssDNA or dsDNA.…”
Section: Introductionsupporting
confidence: 53%
“…However, strong duplex stabilization due to the presence of highly positively charged binding ligands opposes duplex melting, which is an essential part of the nucleic acid chaperone activity of HIV-1 NC. Thus, it is the balance of NC's capability to facilitate annealing through binding to dsDNA with its capability to destabilize GT-rich basepaired regions due to its sequence-specific binding to single-stranded TG sequences, which likely accounts for the enhanced chaperone activity of HIV-1 NCp7 (7,9,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…1). [51][52][53] However, NC-mediated fraying of the NA structure depends on the overall stability of the NA and requires natural mismatches as for wild-type TAR in order to take place. 46,54,57 This NC-mediated fraying of the NA structure largely relies on the hydrophobic plateau of the ZnF domain.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…All experiments are performed in 10 mM Hepes pH 7.5, and 50 mM Na + . Figure is taken from Cruceanu et al 150 structure, aside from two CCHC-type zinc finger motifs. NC binds preferentially to ssDNA, although dsDNA binding is also very strong.…”
Section: Figure 11mentioning
confidence: 99%
“…This insight reveals that the optimal function of NC may represent a tradeoff between strong binding to ssDNA for duplex destabilization and the ability of the protein to bind and unbind rapidly to facilitate rapid reorganization of nucleic acid structure. 150,151 A recent study has also suggested that the dramatic effect of HIV-1 NC on DNA stretching may be used successfully as a test of possible drugs that may target NC and prevent HIV-1 replication. 152 …”
Section: Figure 11mentioning
confidence: 99%